AB1204 Quantitative mri and dynamometers can distinguish myositis from healthy control muscle. (12th June 2018) - Farrow, M.; Biglands, J.; Tanner, S.; Buch, M.; Emery, P.; Grainger, A.; Tan, A.L.
Abstract : Background: Myositis is an autoimmune disease which can decrease quality of life and increase mortality. Clinical presentation includes muscle weakness, changes in muscle microstructure, myosteatosis, raised muscle enzymes and myalgia. Diagnosis is reliant on subjective clinical examinations, blood tests and invasive muscle biopsies. Quantitative MRI techniques such as diffusion tensor imaging (DTI) and fat fraction (FF) measurements offer non-invasive measurements, which could improve the understanding of muscle pathology and potentially inform diagnosis. DTI measures water diffusion within tissues which is sensitive to changes in muscle microstructure (1) . FF provides a quantitative measure of myosteatosis in muscles (2) . The use of these techniques could provide new imaging biomarkers in the diagnosis and management of myositis. Objectives: To evaluate whether fat fraction, mean diffusivity and dynamometer measurements are sensitive enough to detect muscle differences in myositis patients compared to healthy controls. Methods: 10 active myositis patients (6 female, mean age 55±18) diagnosed according to the Bohan and Peter myositis criteria (mean CK 2, 015±10, 787) and 16 healthy controls (10 female, mean age 44±17), were imaged using STEAM-EPI diffusion and 2-point Dixon to obtain FF measurements. Myositis patients included 5 polymyositis, 3 dermatomyositis and 2 inclusion body myositis. Mean measurements of FF and mean diffusivity (MD) were obtained from regions drawn manually within the individual muscles of the quadriceps and hamstrings (image 1). No distinction was made between affected and unaffected muscles. In addition to MRI, all participants had knee extension and flexion power and torque measured on an isokinetic dynamometer and handgrip measurements on an isometric dynamometer. Differences were assessed using independent T-tests. Results: FF and diffusion measurements were higher in myositis patients compared to healthy controls, whereas muscle power and torque were reduced (table 1). These results were consistent across both quadriceps and hamstrings. a) Sagittal (localiser) image of the thigh used in the planning of the Vibe-Dixon imaging volume (shown by the box). b) Regions of interest were drawn corresponding to the individual muscles of the thigh. c) Stimulated echo acquisition mode-Echo planar imaging (STEAM-EPI) diffusion image Conclusions: MRI based FF and DTI measurements and dynamometer measurements can detect muscle differences between myositis and healthy control groups. These differences are consistent with increased myosteatosis, increased oedema and the effects of muscle fibre plasticity. These measures show potential as novel imaging biomarkers in the diagnosis and management of myositis. References: [1] Qi, et al. Journal of magnetic resonance imaging. 2008 [2] Willis, et al. 2013 Disclosure of Interest: None declared